Human Resource Development Practices: Empirical Evidence from Nepal Rastra Bank - Gnawali, Achyut (Kathford Journal of Engineering and Management, 2018)
Human resource development (HRD) is the process of increasing knowledge, skills and capacities of employees. It is concerned with preparing employee to work effectively and efficiently in the organization. It is a complementary approach to other development strategies, particularly employment and reduction of inequalities. It also considers HRD as synonymous with human development, which encompasses education, training, health, nutrition, and fertility reduction. It ensures that organizations have adequate human resources with capabilities needed for achieving goals. This article has tried to explore the practices and relation between HRD and performance of Nepal Rastra Bank.